The timescales of magma evolution at mid-ocean ridges - Brandl, Philipp A.; Regelous, Marcel; Beier, Christoph; O'Neill, Hugh St C.; Nebel, Oliver; Haase, Karsten (Lithos, 2016)
Oceanic crust is continuously created at mid-ocean ridges by decompression melting of the upper mantle as it upwells due to plate separation. Decades of research on active spreading ridges have led to a growing understanding of the complex magmatic, tectonic and hydrothermal processes linked to the formation of new oceanic igneous crust. However, less is known about the timescales of magmatic processes at mid-ocean ridges, including melting in and melt extraction from the mantle, fractional crystallisation, crustal assimilation and/or magma mixing. In this paper, we review the timescales of magmatic processes by integrating radiometric dating, chemical and petrological observations of mid-ocean ridge basalts (MORBs) and geophysical models. These different lines of evidence suggest that melt extraction and migration, and crystallisation and mixing processes occur over timescales of 1 to 10,000 a. High-resolution geochemical stratigraphic profiles of the oceanic crust using drill-core samples further show that at fast-spreading ridges, adjacent flow units may differ in age by only a few 100 a. We use existing chemical data and new major- and trace-element analyses of fresh MORB glasses from drill-cores in ancient Atlantic and Pacific crust, together with model stratigraphic ages to investigate how lava chemistry changes over 10 to 100 ka periods, the timescale of crustal accretion at spreading ridges which is recorded in the basalt stratigraphy in drilled sections through the oceanic crust. We show that drilled MORBs have compositions that are similar to those of young MORB glasses dredged from active spreading ridges (lavas that will eventually be preserved in the lowermost part of the extrusive section covered by younger flows), showing that the dredged samples are indeed representative of the bulk oceanic crust. Model stratigraphic ages calculated for individual flows in boreholes, together with the geochemical stratigraphy of the drilled sections, show that at fast-spreading ridges, magma compositions vary over < 100 to 1000 a, likely due to variations in the relative rates of crystallisation and melt recharge. However, on longer timescales of 10 to 100 ka, variations in the composition of the primitive melt feeding the ridge lead to chemical variations in the erupted lavas, likely as a function of thermal and/or chemical heterogeneity of the mantle source. The further understanding of these temporal variations in magma composition, especially at shorter timescales of less than a few centuries, is a promising area for future research.
Keywords: Crystallisation; Magma evolution; MORB; Ocean drilling; Oceanic crust; Timescales